1998
DOI: 10.1038/sj.onc.1202076
|View full text |Cite
|
Sign up to set email alerts
|

Autophosphorylation of Src and Yes blocks their inactivation by Csk phosphorylation

Abstract: Csk phosphorylates Src family protein tyrosine kinases on a tyrosine residue near their C-terminus and downregulates their activity. We previously observed that this regulation requires a stoichiometric ratio of Csk : Src in a time-independent manner. In this report we examined this unusual kinetic behavior and found it to be caused by Src autophosphorylation. First, pre-incubation of Src with ATP-Mg led to time-dependent autophosphorylation of Src, activation of its kinase activity and loss of its ability to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
82
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(91 citation statements)
references
References 28 publications
(34 reference statements)
4
82
0
Order By: Relevance
“…Phosphorylation of Tyr-419/416 can also activate Src activity in the context of simultaneous phosphorylation at Tyr-530/527 (Boerner et al, 1996;Sun et al, 1998), suggesting that active Src phosphorylated at Tyr-419/416 can not be fully inactivated by phosphorylation at Tyr-530/527 alone. This supports the findings that inactive Src may be the target of other kinases that can phosphorylate Tyr-419/416 and cause Src activation (Chiang and Sefton, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of Tyr-419/416 can also activate Src activity in the context of simultaneous phosphorylation at Tyr-530/527 (Boerner et al, 1996;Sun et al, 1998), suggesting that active Src phosphorylated at Tyr-419/416 can not be fully inactivated by phosphorylation at Tyr-530/527 alone. This supports the findings that inactive Src may be the target of other kinases that can phosphorylate Tyr-419/416 and cause Src activation (Chiang and Sefton, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…30). Furthermore, autophosphorylation permits SFKs to remain active even when their Tyr T is phosphorylated (31). Recently, Lerner and Smithgall (32) reported that human immunodeficiency virus Nef binding or mutations of the SH2 kinase linker caused Hck activation by autophosphorylation even when Tyr T remains phosphorylated and bound to the SH2 domain.…”
Section: Discussionmentioning
confidence: 99%
“…3A) may favor homotypic (26,27) and heterotypic (24,25) protein interactions with c-Src and further enforce c-Src ''opening.'' Indeed, it has been demonstrated that doubly phosphorylated c-Src can be active, such that Y419 phosphorylation can override the p-Y530-directed inhibition (28). The balance of tyrosine kinase (Csk and Chk) and phosphatase (PTP␣) activity, in both basal and stimulated states, is partially responsible for the state of Src activation.…”
Section: Vehicle) (C and D)mentioning
confidence: 99%